Psychological, Social, and Economic Burden of COVID-19: A Comparison of Polish and Portuguese Young Adults - Frączek,Sylwia (2023)
Abstract Introduction: The COVID-19 pandemic has affected all societies, and its effects relate not only to physical health but also to mental health, social relations, and the economic situation of the population all over the world. This research aims at studying the perceptions of changes during the COVID-19 pandemic in mental health, economic situation, and social relations among Polish and Portuguese young. The present study also sought to assess the perception of change during the pandemic in health-related quality of life (HRQoL) among Polish and Portuguese young adults. Methods: A sample of young adults (aged 18-29) from Poland (n = 330) and Portugal (n = 189) filled in an online questionnaire composed of the EQ-5D-5L, some questions from the SHARE COVID-19 questionnaire regarding mental health, social relations, and economic situation, and sociodemographic details. Descriptive analyses, χ2 tests, Student’s t test, and Fisher’s exact test were used to study the existence of differences between Poles and Portuguese. Results: Almost 2 years after the beginning of the pandemic, Polish and Portuguese respondents reported a perceived lower level of HRQoL in comparison to the times before the outbreak of COVID-19. Both Polish and Portuguese respondents perceived an increase in sleeping problems since the outbreak and in loneliness. Respondents from both countries reported a perception of a decrease in the frequency of meeting other people and a perceived economic deterioration. Conclusion: The results indicate what factors are contributing to the worsening of the general living situation of the respondents and show that governments and health authorities should, in addition to the medical consequences of the virus, take the necessary measures to mitigate the long-term consequences of the virus. Authorities should, as well, pay special attention to the group of young adults who, in this uncertain time, are trying to make the most important decisions for their development.